Delivering patient choice in clinical practice: a conversation analytic study of communication practices used in neurology clinics to involve patients in decision-making - Markus Reuber; Merran Toerien; Rebecca Shaw; Roderick Duncan (Health Services and Delivery Research, 2015)
Background: The NHS is committed to offering patients more choice. Yet even within the NHS, the meaning of patient choice ranges from legal ‘rights to choose’ to the ambition of establishing clinical practice as a ‘partnership’ between doctor and patient. In the absence of detailed guidance, we focused on precisely how to engage patients in decision-making. Objectives: To contribute to the evidence-base about whether or not, and how, patient choice is implemented to identify the most effective communication practices for facilitating patient choice. Design: We used conversation analysis to examine practices whereby neurologists offer choice. The main data set consists of audio- and video-recorded consultations. Patients completed pre- and post-consultation questionnaires and neurologists completed the latter. Setting and participants: The study was conducted in neurology outpatient clinics in Glasgow and Sheffield. Fourteen neurologists, 223 patients and 120 accompanying others took part. Results: Patients and clinicians agreed that choice had featured in 53.6% of consultations and that choice was absent in 14.3%. After 32.1% of consultations, either patient or neurologist thought choice was offered. The presence or absence of choice was not satisfactorily explained by quantitatively explored clinical or demographic variables. For our qualitative analysis, the corpus was divided into four subsets: (1) patient and clinician agree that choice was present; (2) patient and clinician agree that choice was absent; (3) patient ‘yes’, clinician ‘no’; and (4) patient ‘no’, clinician ‘yes’. Comparison of all subsets showed that ‘option-listing’ was the only practice for offering choice that was present only (with one exception, which, as we show, proves the rule) in those consultations for which participants agreed there was a choice. We show how option-listing can be used to engage patients in decision-making, but also how very small changes in the machinery of option-listing [for instance the replacement or displacement of the final component of this practice, the patient view elicitor (PVE)] can significantly alter the slot for patient participation. In fact, a slightly modified form of option-listing can be used to curtail choice. Finally, we describe two forms of PVE that can be used to hand a single-option decision to the patient, but which, we show, can raise difficulties for patient choice. Conclusions: Choice features in the majority of recorded consultations. If doctors want to ensure a patient knows she or he has a choice, option-listing is likely to be best understood by patients as an invitation to choose. However, an important lesson from this study is that simply asking doctors to adopt a practice (like option-listing) will not automatically lead to a patient-centred approach. Our study shows that precisely how a practice is implemented is crucial. Future research: Future research should investigate (1) links between the practices identified here and relevant outcome measures (like adherence); (2) whether being given a choice is better or worse for patients than receiving a doctor’s recommendation, taking account of clinical and demographic factors; and (3) how our approach could be fruitfully applied in other settings. Funding: The National Institute for Health Research Health Services and Delivery Research programme.